2D Animation Storyboard Design "Mira and The Batik Fairy: Batik Sawat Pengantin Cirebon for Children" - Lionardi, Angelia; Lawe, I Gusti Agung Rangga; Aulia, Farah; Firdaus, Yasmin Zahra; Tobing, Sheril Luthfiana (Rekam, 2023)
Batik, a cultural artifact full of philosophical values, is now seen as just a part of fashion style and a sweetening element. Many people, especially children, do not understand the symbolic meanings of the aesthetic elements of batik. This problem is commonplace in Indonesia, including Cirebon. As batik centers, only a few schools in Cirebon provide opportunities for their students to learn batik. If the meaning of batik is to be taught to the younger generation, then an approach using new media can be an alternative to introduce it persuasively. One medium that is close and has the potential to introduce batik to children is 2D animation. The research method that will be used is qualitative. The animation process starts with several stages, from collecting data about the batik we want to make into a story theme: Batik Sawat Pengantin Cirebon. Data collection was done by direct observation and interviews. After the data is collected, the next step is to search for story ideas, create scenarios, design visual concepts, and create storyboards. Then, the animation production process can be carried out. This research will focus on the storyboard design part, namely the clean-up storyboard and animatic storyboard, which will guide in making 2D animation.